Use and treatment experiences of alcohol and substance addicts during the covid-19 pandemic - Semerci, Melike; Acar, Burak; Yaman, Ömer Miraç (Journal of Dependence, 2022)
Objective: The population of addicts, which is among the disadvantaged and vulnerable groups in the society, makes up one of the groups affected by the pandemic. In this regard, it was aimed to evaluate the life experiences and treatment-related conditions the individuals addicted to alcohol and substances have during the pandemic. Method: Within this framework, in-depth interviews have been carried out using the semi-structured interview technique with a total of 15 people: 10 professionals, trainers and ex-users working with addicts, and 5 addicts who still continue their treatment processes. Results: The pandemic caused some positive/negative changes in the lives of individuals that are addicted to alcohol and substances, and these changes were mainly manifested in social isolation, substance supply and treatment services. In addition, it has also been determined that social isolation brings along negative situations such as anxiety, stress and unemployment for the addicts, and these individuals experience difficulties especially when it comes to carrying on with the treatment services and adapting to the alternative methods that are being applied. Conclusion: In this respect, the addicts, who make up a vulnerable group in the general population, should be considered as a sensitive area especially during the pandemic, and institutional and systemic intervention plans should be carried out comprehensively to eliminate the negative experiences that are being faced during this period.